INFORMATION PROVISION OF DECISION SUPPORT SYSTEMS IN CONDITIONS OF STRUCTURAL CHANGES AND DIGITALIZATION OF THE ECONOMY - Vertakova, Yulia; Mkrtchyan, Vardan; Leontyev, Eugene (Journal of Applied Engineering Science, 2019)
The article was devoted to the research of methodological and practical aspects of the development and application of information support for decision-making tools to improve the competitiveness of enterprises, which together constitute a system for supporting decision-making and managing competitiveness. The algorithm for working with decision support tools in the competitiveness management process was developed and implemented, which includes the solution of the following tasks: analysis of the market situation, data collection, selection and analysis of competitor data based on BigData technology, selection of competitive pairs, modeling and forecasting of enterprises , analysis, assessment and selection of factors of influence on competitiveness, synthesis of scenarios of enterprise development, predictive modeling of dynamics of competitive indicators, the analysis of simulation results, the selection vectors factor values for the optimal development strategy, the selection of recommendations for achieving optimal values of the indicators of competitiveness, the synthesis of the recommendations of the selection rules, the provision of advice to decision-makers.